Sub-regional and constitutional protection of socio-economic rights: SADC, Botswana, Lesotho, Malawi, Namibia, and Zimbabwe - Moyo, Admark (Malawi Law Journal, 2016)
A survey of five domestic constitutions in Southern Africa shows that only the Malawian and Namibian Constitutions recognise some socio-economic rights as justiciable rights. The Constitution of Lesotho recognises socio-economic rights as principles of state policy. Zimbabwe and Botswana provide classic examples of countries in which socio-economic rights have been relegated to the margins of legal protection. Save for the right to own property, no other socio-economic rights are protected in these countries' Constitutions. However, in all these countries, the courts have demonstrated some resolve and innovativeness in interpreting some civil and political rights in order to protect certain socio-economic interests, such as by holding that the right not be subjected to torture or inhuman or degrading punishment or treatment includes a duty on the state to provide access to basic amenities of life. Such decisions offer some hope for the judicial enforcement of socio-economic rights, and for these states to fulfil the promises they have made at the sub-regional level.